Migración, desarrollo y condicionalidad: marcos políticos y narrativos - Augusto Delkáder-Palacios (Revista Iberoamericana de Estudios de Desarrollo)
This study aims to offer a better conceptual understanding of the relationship between migration and development. To do this, we will analyze the framing of migrations as a central element of approaches and policies on migration and development. We will identify three frames on migration that lead to three approaches or policy frames on migration and development: the «restrictive approach», the «selective approach», and the «expansive approach». We will focus on the motivations and political effects of these migration and development approaches and, particularly, in relation to migration-related conditionality. Finally, we will place the analysis in the case of the European Union.